Indigenous Specializations: Dreams, Developments, Delivery and Vision - Richardson, Kinewesquao/Cathy; Thomas, Qwul'sih'yah'maht/Robina; Green, Kundoque/Jacquie; Ormiston, Naadli/Todd (The Australian Journal of Indigenous Education, 2012)
This article documents the establishment of the Indigenous Specializations program in the School of Social Work at the University of Victoria. In the absence of funding for Indigenous programs, First Nations professors Robina Thomas and Jacquie Green developed the Indigenous Specializations program ‘off the side of their desk’. This article describes the process of creating a culturally specific program for Indigenous students in a mainstream university. Many of the challenges depicted in the article are ongoing, alongside various successes and victories for Indigenous graduates.